Exponential turnpike property for particle systems and mean-field limit - Michael Herty; Yizhou Zhou (European Journal of Applied Mathematics)
This work is concerned with the exponential turnpike property for optimal control problems of particle systems and their mean-field limit. Under the assumption of the strict dissipativity of the cost function, exponential estimates for both optimal states and optimal control are proven. Moreover, we show that all the results for particle systems can be preserved under the limit in the case of infinitely many particles.